2009
DOI: 10.1038/onc.2009.166
|View full text |Cite
|
Sign up to set email alerts
|

Impaired p53 binding to importin: a novel mechanism of cytoplasmic sequestration identified in oxaliplatin-resistant cells

Abstract: Previous studies have described one nuclear localization signal (NLSI) in p53 and speculated on two additional sites termed NLSII and NLSIII. Drug-resistant KB cells selected with cisplatin or oxaliplatin were found to have increased p53 levels and in oxaliplatin-selected cells, a larger p53 predominantly in the cytoplasm. In oxaliplatin-selected cells a single nucleotide deletion in the sequence-encoding amino acid 382, part of NLSIII, resulted in a frame shift and a 420 amino acid protein (p53 420 ). We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Sequestration of p53 in the cytoplasm has also been implicated in oxaliplatin-resistant cervical carcinoma cell survival (50), supporting the principle of cytoplasmic sequestration of p53 in the inhibition of apoptosis. However, it is unclear whether the shift in p53 localization in melanoma may be a consequence of increased nuclear export and/or decreased nuclear import/tethering within the cytoplasm.…”
Section: Discussionmentioning
confidence: 96%
“…Sequestration of p53 in the cytoplasm has also been implicated in oxaliplatin-resistant cervical carcinoma cell survival (50), supporting the principle of cytoplasmic sequestration of p53 in the inhibition of apoptosis. However, it is unclear whether the shift in p53 localization in melanoma may be a consequence of increased nuclear export and/or decreased nuclear import/tethering within the cytoplasm.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that a p.K382fs mutation resulting in a 420 aa protein showed cytoplasmic localization owing to impaired binding to importin. This occurred because of conformational changes from the additional 27 aa and not from any alteration in the nuclear localization domains . In addition, specific p53 mutants may undergo post‐translational modifications that can stimulate nuclear transport and/or mitochondrial association, promoting cytoplasmic accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this function, NORAD indeed stimulates the TGF‐β signaling pathway by two mechanisms first, stimulating nuclear translocation of SMAD2/3 where NORAD promotes the interaction of phosphorylated SMADs with importin proteins particularly importin 7 and importin β1 which play an important role in translocation of SMADs from cytoplasm to nucleus and second, increasing the expression of SMAD2 and EMT markers in long‐term . Moreover, it has been shown that importin β1 recognizes nuclear localization signals and mediates entry of some other proteins involved in pathways other than TGF‐β signaling, including the STAT3 and p53 pathways . Therefore, NORAD may affect the Janus kinase/signal transducer and activation of transcription (JAK/STAT) and P53 signaling pathways in the same mechanism as in the TGF‐β signaling pathway.…”
Section: Lncrnas and Receptor Serine Kinases (Tgf‐β)mentioning
confidence: 99%